2018
DOI: 10.1080/09674845.2018.1459147
|View full text |Cite
|
Sign up to set email alerts
|

The gamma-glutamyl transferase to platelet ratio and the FIB-4 score are noninvasive markers to determine the severity of liver fibrosis in chronic hepatitis B infection

Abstract: Objective Noninvasive liver fibrosis evaluation is an important issue in chronic hepatitis B infection, and may be assessed using transient elastography (Fibroscan) or with blood markers. We compared the value of Fibroscan with that of a panel of routine serum markers. Materials and methods We recruited 278 chronic hepatitis B patients who underwent Fibroscan and HBV DNA testing. Fibroscan assessments were made, and blood taken for the measurement of the gamma-glutamyl transferase (GGT) to platelet ratio (GPR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 26 publications
2
15
0
1
Order By: Relevance
“…In agreement with these findings, Lee et al [56] also showed that GPR and FIB-4 can significantly screen the liver fibrosis status in CHB patients and that GPR displayed the best diagnostic performance.…”
Section: Crp To Albumin Ratio (Car)supporting
confidence: 58%
“…In agreement with these findings, Lee et al [56] also showed that GPR and FIB-4 can significantly screen the liver fibrosis status in CHB patients and that GPR displayed the best diagnostic performance.…”
Section: Crp To Albumin Ratio (Car)supporting
confidence: 58%
“…On the other hand, it should be noted that the findings presented in this study indicate the inability of predicting the severity of hepatic fibrosis among PSC patients based on the platelet-dependent models such as aspartate aminotransferase-to-platelet ratio index, gamma-glutamyl transferase-to-platelet ratio, fibrosis index based on the 4 factors, and red blood cell distribution width-to-platelet ratio. [51][52][53][54][55] Therefore, in the PSC-C patients, this context of platelet count status should be considered in the application of models predicting progression to cirrhosis. Recently, in a large cohort of PSC patients from the United Kingdom (UK-PSC score), a new risk scoring model was developed in order to predict the outcome of patients diagnosed with PSC.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the combined analysis of liver enzymes and platelet counts has provided important information regarding the role of new biomarkers in predicting neoplastic and infectious disease severity [47, 48]. One of these biomarkers, the APRI, has been widely studied as a minimally invasive marker of fibrosis and inflammation in hepatic disease [49, 50].…”
Section: Discussionmentioning
confidence: 99%